Sintering densification mechanism of binder jet 3D printing 316L stainless steel parts via dimensional compensation technology - Zhiping Chen; Bingbing Wan; Junchen Liu; Dezhi Zhu; Hao Wang; Weiping Chen; Runxia Li; Zhenfei Jiang; Fangfang Liu (Journal of Materials Research and Technology)
The dimensional compensation technology can achieve high dense metal parts with precise dimensions for binder jet 3D printing (BJ3DP). In this study, two models (cuboid and gear) of BJ3DP 316L stainless steel (BJ3DP316LSS) parts were established. Numerical simulation and experimental volume shrinkage of the BJ3DP316LSS sintered parts via dimensional compensations technology were investigated. When the dimensional compensation coefficient was set as 1.25, the BJ3DP316LSS cuboids and gears exhibited high densification as 99.6% and 99.4%, respectively. The experimental dimension deviation rates of cuboid and gear parts after dimensional compensations ranged from −3.56% to −0.15% and from 0.89% to 3.42%, respectively. Due to twinning-induced plasticity mechanism, the BJ3DP316LSS sintered gear part via dimensional compensation technology exhibited high hardness (∼139 HV), high yield strength (∼249 MPa), high ultimate tensile strength (∼546 MPa) and excellent elongation (∼62%), which are higher than those of the reported 316LSS samples.